(untitled) (Praxis Educativa, 2021)
The article aims to reconstruct the formative-disciplinary practices that occur in the territories for disciplinary research in Education Sciences undergraduate course. For the development of the work, we position ourselves in a qualitative methodology, specifically in the case studies. In this sense, the cases selected for this study were two teams from the subjects General Didactics and History of Argentine Education, which were reconstructed from in-depth interviews with directors, researchers, undergraduate and graduate students. We fully identified three formative territories for disciplinary research: the field, the office, and the extra-institutional territories, in each of which diverse pedagogical links were configured according to the limits imposed by the epistemology of the discipline. Although each formative territory has singular connotations, there is a dialectic among them that feeds back, communicates and constitutes them.